Annotated mitochondrial genome assemblies for two sand lances (genus: Ammodytes) from the northwest Atlantic. (1st November 2016) - Horne, John B.; Mcbride, Meghan C.; Lighten, Jackie; Bradbury, Ian R.; Bentzen, Paul
Abstract: Complete mitochondrial genomes of two northwest Atlantic sand lances ( Ammodytes americanus and Ammodytes dubius ) were sequenced, assembled, and annotated. Both genomes were 16 519 bp in length and were differentiated by a genetic distance of only 0.01. Furthermore, mitochondrial gene annotations were identical for both species. Phylogenetic analysis revealed that divergence between the two species was shallow, relative to other members of the genus.